Implementasi Prinsip-prinsip Manajemen Keuangan Sekolah di SD Ar-Rahman Motik Jakarta Selatan - Basuki, Gayatri; Ahmad, Masduki (AS-SABIQUN, 2023)
School financial managemet is carried out by the school principal, consists of financial planning, financial allocation and financial reporting activities. School financial management will work well if it can apply the principles of financial management, namely transparency, accountability, effectiveness, and efficiency. The aim of this study is to find out the implementation of the principles of financial management in private elementary school. This study used a qualitative methos with a descriptive approach to explore social conditions that occus as a whole. Participant in this study were one school principal at private elementary school in South Jakarta. The result of this study are, financial management in elementary school is running well, the school principal applies the principles of transparency and accountability in financial planning and reporting, as well as school activities running effectively and efficiently in accordance with the budget plan. Another factor that has a positive impact on the effectiveness of school financial management is the amount of experience the school principle has.